Protective Effect of The Extract of Dayak Onions (Eleutherine palmifolia) on Sertoli and Leydig Cell Necrosis in Mice (Mus Musculus) Induced with Monosodium Glutamate - Rahmatullah, Aldin Akbar; Ratnaningtyas, Nurrohmah; Sugihartuti, Rahmi; Susilowati, Suherni; Safitri, Erma; Mulyati, Sri (Universitas Airlangga, 2024)
This study aims to determine the effect of the extract of Dayak onions (Eleutherine palmifolia) on the number of necrotic Sertoli and Leydig cells in mice (Mus musculus) induced with monosodium glutamate (MSG). This study involved 25 male mice aged 11 weeks and weighing approximately 20 g. The mice were divided into five groups, namely C- (0.5% CMC-Na), C+ (4 mg/g BW of MSG and 0.5% CMC-Na), T1 (4 mg/g BW of MSG and 30 mg/kg BW of Dayak onion extract), T2 (4 mg/g BW of MSG and 60 mg/kg of Dayak onion extract), and T3 (4 mg/g BW of MSG and 120 mg/kg BW of Dayak onion extract). All treatments were administered for 52 days. The mice were euthanized on day 53 of the experiment. Their testicles were removed and used to prepare histological specimens with the H&E staining method. The results showed significant differences (p < 0.05) in the number of necrotic Sertoli and Leydig cells between the C+ group and the T1, T2, and T3 groups with gradually decreasing values. The results suggested that the administration of the extract of Dayak onions can prevent Sertoli and Leydig cell necrosis in mice induced with MSG at an optimal dose of 120 mg/kg BW.